Management of water as a national resource for sustainable development - Ramaswamy, P.R. (2003)
Sustainable development is the need of the hour in the developed and developing countries because of the current onslaught of globalisation. The powers of money and market have begun to distort democracy and the natural resources are being exploited to meet the ever-increasing requirements and aspirations of the human race. The results are that while the human civilisation is being threatened from within by its own internal contradictions, the external environment is also being destroyed at a pace that outstrips its regeneration. It is, therefore, necessary to evolve a strategy to synchronise the solutions to these threats. The conservation of water is one important strategy. - Reproduced.
Keywords: Sustainable development; Water resources management